1984
DOI: 10.1111/j.1365-2621.1984.tb13225.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Extended Cook Times on Certain Physical and Chemical Characteristics of Beef Prepared in a Waterbath

Abstract: Contralateral beef muscles were prepared in either a 60°C waterbath or a 94°C conventional oven. Waterbath cooked muscles were placed in nylon bags and evacuated prior to cooking; some samples were held in the bath for 2 or 4 additional hours after reaching internal end-point temperature. Yields were greatest for waterbath prepared samples which were removed from the bath immediately upon reaching internal end-point temperature. Extended cooking times increased collagen solubilization and decreased yields, ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
1
2

Year Published

1986
1986
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 14 publications
3
14
1
2
Order By: Relevance
“…Warner-Bratzler Shear values were similar among the cooked roasts and control ( Table 2). The Warner-Bratzler shear values obtained for the conventional and waterbath cooked roasts were comparable to those reported by Dinardo et al (1984) and Stites et al (1989). Smokehouse roasts took the longest to cook and were exposed to moving air during the process, but the roasts did not have a significantly higher cooking loss compared to the other cooked roasts ( Table 2).…”
Section: Resultssupporting
confidence: 79%
“…Warner-Bratzler Shear values were similar among the cooked roasts and control ( Table 2). The Warner-Bratzler shear values obtained for the conventional and waterbath cooked roasts were comparable to those reported by Dinardo et al (1984) and Stites et al (1989). Smokehouse roasts took the longest to cook and were exposed to moving air during the process, but the roasts did not have a significantly higher cooking loss compared to the other cooked roasts ( Table 2).…”
Section: Resultssupporting
confidence: 79%
“…Shear force values, however, showed a small decrease for muscles from the round (Dinardo et al, 1984). The cooking times used by these workers (Dinardo et al, 1984) were considerably shorter than the cooking times used in this present paper. This suggested that much of the gain in increased tenderness with extended cooking could be counterbalanced by significant losses in juiciness and flavor.…”
Section: Interpretation Of Resultscontrasting
confidence: 64%
“…Cooking losses of about 30% would occur in 48 hr at 60°C and, if a further cooking was required, then total losses as high as 40% might be expected. Dinardo et al (1984) have recently shown that holding meat at 60°C for up to 4 hr decreased subjectively determined juiciness and flavor without having any significant effect on tenderness. Shear force values, however, showed a small decrease for muscles from the round (Dinardo et al, 1984).…”
Section: Interpretation Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, few publications dealt with the storage stability of these products (Church & Parsons, 1993; Hansen et al ., 1995). However, a number of investigations about technological characteristics, sensory quality and shelf‐life stability of s ous vide and vacuum cook‐in bag meat have been published (Buck et al ., 1979; Dinardo et al ., 1984; Smith & Alvarez, 1988; Stites et al ., 1989; Cooksey et al ., 1990; Hansen et al ., 1995; Bertelsen & Juncher, 1996; Church, 1996; Thorsell, 1996; Palka & Daun, 1999; Vaudagna et al ., 1999; Church & Parsons, 2000).…”
Section: Introductionmentioning
confidence: 99%